Deletion of psychiatric risk gene Cacna1c impairs hippocampal neurogenesis in cell-autonomous fashion - Völkening, Bianca; Bartsch, Dusan (Glia, 2017)
Ca2+ is a universal signal transducer which fulfills essential functions in cell development and differentiation. CACNA1C, the gene encoding the alpha-1C subunit (i.e., Cav1.2) of the voltage-dependent l-type calcium channel (LTCC), has been implicated as a risk gene in a variety of neuropsychiatric disorders. To parse the role of Cav1.2 channels located on astrocyte-like stem cells and their descendants in the development of new granule neurons, we created TgGLAST-CreERT2/Cacna1cfl/fl/RCE:loxP mice, a transgenic tool that allows cell-type-specific inducible deletion of Cacna1c. The EGFP reporter was used to trace the progeny of recombined type-1 cells. FACS-sorted Cacna1c-deficient neural precursor cells from the dentate gyrus showed reduced proliferative activity in neurosphere cultures. Moreover, under differentiation conditions, Cacna1c-deficient NPCs gave rise to fewer neurons and more astroglia. Similarly, under basal conditions in vivo, Cacna1c gene deletion in type-1 cells decreased type-1 cell proliferation and reduced the neuronal fate-choice decision of newly born cells, resulting in reduced net hippocampal neurogenesis. Unexpectedly, electroconvulsive seizures completely compensated for the proliferation deficit of Cacna1c deficient type-1 cells, indicating that there must be Cav1.2-independent mechanisms of controlling proliferation related to excitation. In the aggregate, this is the first report demonstrating the presence of functional L-type 1.2 channels on type-1 cells. Cav1.2 channels promote type-1 cell proliferation and push the glia-to-neuron ratio in the direction of a neuronal fate choice and subsequent neuronal differentiation. Cav1.2 channels expressed on NPCs and their progeny possess the ability to shape neurogenesis in a cell-autonomous fashion.
Gesehen am 30.04.2018